الآثار التاریخیة لمدينة دمشق خلال رحلتي ابن جبير وابن بطوطة : Historical Monuments of Damascus in the light of the Travelogues of Ibn Jubair and Ibn Battūta - Aatika Aslam; Prof. Dr. Sheik Shafiq-ur-Rehman (Al-Qamar, 2020)
Everything has an end and nothing is eternal in this world. Some people come and others are annihilated. These annihilated nations leave their inscriptions, historical and religious monuments and other remaining’s which become cultural and intellectual symbol for later generations. Damascus is one of the oldest inhabited cities in the world which is closely linked with important historical events, ideas, traditions and traces of earlier cultures especially from the Islamic period. It also testifies to the unique aesthetic achievements of the civilizations as well as it exhibits outstanding evidences of the civilizations which created it. In this regard traveller’s travelogues plays a very important role to get accurate records of particular peoples, places, customs and ceremonies etc. We see that travellers towards Damascus paid their best efforts to give an account of the prevalent social milieu and a deep insight into their culture, habitation and historical and religious monuments which is important not only for Muslims but also for other religions. This article is a comparative study of Damascus’ historical and religious monuments in the light of the travelogues of Ibn Jubair and Ibn Battūta which specially discusses the existence of these Places, their history and geography such as the Tomb of Maryam, cave of Prophet Ibrahim, Qubūr al-Shuhadāʻ, the Mosque of al-Qadam and Umayyad Mosque etc.